(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Klebsiella pneumonia was seen in hospital acquired pneumonia and became a prominant agent with high antibiotic resistance in community acquired pneumonia. Objectives: We conducted this cross-sectional descriptive study in Thong Nhat hospital from January 2017 to December 2021 to aim at finding out the clinical characteristics and antibiotic resistance of Klebsiella pneumonia on pneumonia. Method: We enrolled 270 pneumonia patients caused by Klebsiella pneumonia who were treated at Thong Nhat hospital. They were divided into two groups based on hospital acquired pneumonia and community acquired pneumonia. Results: Among 270 pneumonia patients who were caused by K.pneumonia, there were 146 cases of community acquired pneumonia (54.1%) and 124 cases of hospital acquired pneumonia. There were 106/270 cases infected by ESBL producing K.pneumonia (39.3%). Males accounted for 65.9%, mean age was 81.29 ± 8.48 years. The symptoms such as fever, cough, purulent sputum secretion, shortness of breath, crackle lung sound and consolidation were more common in patients with hospital acquired pneumonia than community acquired pneumonia, p<0.05. Multiple lobe infiltration was prominent (82.6%), the community acquired pneumonia group recorded more new abnormalities on Chest Xray (97.9%), p< 0.001. The ratios of antibiotic resistance were higher in the hospital acquired pneumonia group with MDR, XDR, and PDR at 31.5%, 50.8%, and 4.9%, respectively. ESBL K. pneumonia in hospital acquired pneumonia highly resistance to carbapenems antibiotic (p < 0.05). Conclusions: K.pneumonia pneumonia often has clinical symptoms, cough, chest pain, shortness of breath, coughing and crackled lung sound. The rate of antibiotic-resistant bacteria was quite high, especially in hospital acquired pneumonia groups.